Tafsir Konstitusional Pengujian Peraturan di Bawah Undang-Undang - Inna Junaenah (The Constitutional Court of the Republic of Indonesia, 2016)
Particular problem in judicial review frequently found is there a contradiction between the subsidiary legislation and the constitution. Unfortunately, in several Supreme Court verdict on judicial review, there is no usage of constitutional interpretation on their legal reasoning. However within domain of Supreme Court authority, constitution is not the touchstone, but constitution perspective must be included to maintain consistency of legislation hierarchy. There are two reasons on that posibilities, first the approximation of constitutional review by the court and second, the consequences of Indonesian’s legal system that implementing legislation hierarchy. Responsibility as the guardian of constitution not only applied on Constitutional Court, but on all the state institutions including every citizen. In the context of guarding consistency of legislation hierarchy, Supreme Court might also develop constitutional interpretation in order to ensure conformity regulations that is examined to the constitution. In addition, meaning of the constitution can be developed by a judge that can be found in accordance with contextuality. The perspective is assessed to highlight more detailed the mapping of the use of constitutional interpretation on Judicial Review in supreme court post amandment of Constitution of Republic Indonesia 1945. This article formulatesthe notion of constitutional interpretation on Judicial Review. Within this concept, will be prepared by the use of mapping of constitutional interpretation on Judicial Review in supreme court post amandment of Constitution of Republic Indonesia 1945. Thus this research was intended to make the judge use constitutional interpretation. Of course if the recommendations are applied, it can be achieved not instantly in a short time. With the use of Constitutional interpretation on Judicial review in supreme court, the constitutionallity can be reflected later on legislation hierarchy as a whole legal system.